Music for Cells? A Systematic Review of Studies Investigating the Effects of Audible Sound Played Through Speaker-Based Systems on Cell Cultures. (March 2022) - Kwak, Dongho; Combriat, Thomas; Wang, Chencheng; Scholz, Hanne; Danielsen, Anne; Jensenius, Alexander Refsum
There have been several studies investigating whether musical sound can be used as cell stimuli in recent years. We systematically searched publications to get an overview of studies that have used audible sound played through speaker-based systems to induce mechanical perturbation in cell cultures. A total of 12 studies were identified. We focused on the experimental setups, the sounds that were used as stimuli, and relevant biological outcomes. The studies are categorized into simple and complex sounds depending on the type of sound employed. Some of the promising effects reported were enhanced cell migration, proliferation, colony formation, and differentiation ability. However, there are significant differences in methodologies and cell type-specific outcomes, which made it difficult to find a systematic pattern in the results. We suggest that future experiments should consider using: (1) a more controlled acoustic environment, (2) standardized sound and noise measurement methods, and (3) a more comprehensive range of controlled sound parameters as cellular stimuli.